Evaluating socioemotional skill interventions for preschool children with autism spectrum disorder: a systematic review - Richard Rickie Akat; Suziyani Mohamed; Nurul Khairani Ismail (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study aims to systematically review and synthesize recent empirical evidence on socioemotional skill interventions for preschool children with autism spectrum disorder (ASD) from an educational evaluation perspective. Guided by the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework, a systematic search of Scopus and Web of Science (WoS) identified 15 peer-reviewed studies published between 2019 and 2025. The included studies were thematically analyzed and appraised using the mixed methods appraisal tool (MMAT). The findings revealed three dominant intervention themes: i) relationship-based and developmental interventions; ii) structured and skill-focused interventions; and iii) creative, expressive, and technology-supported approaches, demonstrating overall positive effects on socioemotional outcomes. However, the strength of evidence remains moderate due to methodological heterogeneity, small sample sizes, and limited longitudinal designs. These findings highlight the importance of developmentally appropriate and flexible intervention designs in inclusive early childhood education. The review offers practical implications for educators, curriculum developers, and policymakers. Specifically, it emphasizes the need for evidence-based socioemotional programs to strengthen inclusive preschool practices for children with ASD.